2011
DOI: 10.1063/1.3610552
|View full text |Cite
|
Sign up to set email alerts
|

Multi-field/multi-scale turbulence response to electron cyclotron heating of DIII-D ohmic plasmas

Abstract: The multi-field=multi-scale core (q $ 0.5-0.8) turbulence response to electron cyclotron heating (ECH) of DIII-D Ohmic plasmas is reported for the first time. Long wavelength (low-k) electron temperature (T e T e ) and high-k density turbulence levels (ñ e =n e ) are observed to strongly increase during ECH. In contrast, low-k and intermediate-kñ e =n e showed little change, whereas the crossphase between local low-k electron temperature and density fluctuations (a n e T e ) was significantly modified. The inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Extensive validation has been performed on the quasilinear growth rates and frequencies [54,58], quasilinear cross-phases [59] and nonlinear fluxes [60,61]. The switch settings used for the predictive modelling with QuaLiKiz are listed in table 6 in appendix C.…”
Section: (I) Tglfmentioning
confidence: 99%
“…Extensive validation has been performed on the quasilinear growth rates and frequencies [54,58], quasilinear cross-phases [59] and nonlinear fluxes [60,61]. The switch settings used for the predictive modelling with QuaLiKiz are listed in table 6 in appendix C.…”
Section: (I) Tglfmentioning
confidence: 99%
“…Investigation of the role of electron temperature gradient modes in electron heat transport in TCV plasmas significant electron heat transport [3]. Indeed, from the experimental side, a correlation between the increase of the electron heat flux q e and the increase of high-k density fluctuations has been reported in [4][5][6][7][8]. Modelling plasmas featuring ETGs by means of gyrokinetic (GK) [9] codes can give an insight on the impact that they have on the turbulent transport.…”
Section: Nuclear Fusionmentioning
confidence: 99%
“…The study of the transport and plasma turbulence during ECRH directly implicates ITER [7], where ECRH is one of the vital heating systems. The electron thermal transport diffusivities and plasma turbulence have been studied in DIII-D for different cases, including ECRH in ohmic plasmas [8], low-confinement mode (L-mode) plasmas [9], and high-confinement mode (H-mode) plasmas [10]. Experimental results from DIII-D found that long-wavelength electron temperature fluctuations play an important role in determining electron thermal transport in L-mode plasmas [9] and H-mode plasmas [10].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results from DIII-D found that long-wavelength electron temperature fluctuations play an important role in determining electron thermal transport in L-mode plasmas [9] and H-mode plasmas [10]. Additionally, it was found that the high-k density fluctuation level can also have a significant effect on the electron thermal transport [8]. To determine the connection between plasma turbulence and heat transport, more detailed experimental work is required.…”
Section: Introductionmentioning
confidence: 99%